Composition and Determinants of Rural Non-Farm Employment in Darjeeling District of West Bengal, India (Economic Journal of Nepal, 2014)
The RNFS has gained immense attention as an effective source of creating additional employment opportunities and generating income in the rural areas and thereby stimulating further growth in rural economies. Based on primary data collected through field survey from Darjeeling district of West Bengal, this study is and Endeavour to understand the composition and the determinants of rural non-farm employment in the Hill Regions of Darjeeling district. Binary Logit Model and Multinomial Logit Model have been employed for the purpose of identifying the determinants non-farm employment. The Study shows that the probability of choosing non-farm sector are significantly affected by factors like age, sex, educational attainment, household's asset value, access to loan and by ownership to land. The relationship between land holding and the incidence of non-farm employment depicted a negative relationship implying that the marginalization of landholding in the study area is one of the important factors that has pushed the workers towards non-farm activities. It is also found that the attainment of higher education is an important factor for choosing regular non-farm activities.